Association Between Kidney Stones and Risk of Stroke: A Nationwide Population-Based Cohort Study. Issue 8 (February 2016) - Lin, Shih-Yi; Lin, Cheng-Li; Chang, Yen-Jung; Hsu, Wu-Huei; Lin, Cheng-Chieh; Wang, I-Kuan; Chang, Chiz-Tzung; Chang, Chao-Hsiang; Lin, Ming-Chia; Kao, Chia-Hung
Abstract : Abstract: Nephrolithiasis is highly prevalent and has been associated with vascular diseases such as cardiovascular events. Few studies have comprehensively associated renal stones with stroke. This study explored whether patients with renal stones were at a higher stroke risk than those without renal stones. A national insurance claim dataset of 22 million enrollees in Taiwan was used to identify 53, 659 patients with renal stones, and 214, 107 were selected as age-, sex-, and comorbidity-matched controls for a 13-year follow-up. The relative stroke risk for the RS cohort was 1.06-fold higher than that for the non-RS group (95% confidence interval [CI] = 1.01–1.11). Age-specific analysis revealed that the adjusted stroke risk for the RS cohort increased as age decreased, with the highest risk of 1.47-fold (95% CI = 1.10–1.96) in patients aged 20 to 34 years, followed by a 1.12-fold risk (95% CI = 1.00–1.25) in patients aged 35 to 50 years. Sex-specific analysis clarified that women in the RS group had a 1.12-fold stroke risk compared with women in the non-RS group (95% CI = 1.03–1.21). Patients who had undergone >4 surgeries had up to 42.5-fold higher risk of stroke (95% CI = 33.8–53.4). The study utilized the national database and demonstrated that patients, particularly women and the younger population, with nephrolithiasis have an increased risk of ischemic stroke development. Patients treated with medication or through surgery for RSs showed steady and higher risks of stroke than those without surgical or medical intervention.